2011
DOI: 10.1111/j.1747-0803.2011.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Atresia with Ventricular Septal Defect and Multifocal Pulmonary Blood Supply: Does an Intensive Interventional Approach Improve the Outcome?

Abstract: Combining surgical unifocalization procedures with subsequent early and intensive catheter-based pulmonary artery rehabilitation may improve vascular growth, ultimately rendering many patients suitable for fenestrated VSD closure. Risk stratification, including intraoperative exit angiography, is essential to determine the need for early transcatheter interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Two patients in this study had residual VSDs due to fenestrated patch closures. In these circumstances, VSD closure is performed using a fenestrated or valved patch to reduce the risk of right heart decompensation [12, 13]. After postoperative stabilization and further interventional management of hypoplastic or stenotic pulmonary arteries, VSD closure may be necessary at a later date.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients in this study had residual VSDs due to fenestrated patch closures. In these circumstances, VSD closure is performed using a fenestrated or valved patch to reduce the risk of right heart decompensation [12, 13]. After postoperative stabilization and further interventional management of hypoplastic or stenotic pulmonary arteries, VSD closure may be necessary at a later date.…”
Section: Discussionmentioning
confidence: 99%
“…Learn et al reported that multiple interventions are essential for this entity. 11 Catheter interventions were carried out 11 times for our five patients with focal pulmonary stenosis before the palliative intra-cardiac repair, and over 20 times after the palliative intra-cardiac repair. Surgical interventions for focal pulmonary stenosis were also carried out in two patients after the palliative intra-cardiac repair.…”
Section: Discussionmentioning
confidence: 99%